Effective Exchange Rates in Central and Eastern European Countries: Cyclicality and Relationship with Macroeconomic Fundamentals - Daniel Stavárek; Cynthia Miglietti (Review of Economic Perspectives, 2015)
This paper examines the evolution of effective exchange rates in nine Central and Eastern European countries in terms of development trends, volatility and cyclicality. Consequently, it provides direct empirical evidence on the nature of the relationship between effective exchange rates and selected macroeconomic fundamentals, addressing a key precondition of numerous exchange rate determination models and theories that attempt to explain the role of exchange rates in the economy. The results suggest that flexible exchange rate arrangements are reflected in both nominal and real effective exchange rates having higher volatility and variability. Furthermore, the results provide mixed evidence in terms of intensity, direction and cyclicality, but show a weak correlation between exchange rates and fundamentals. Sufficiently high coefficients are found only for money supply. Consequently, using fundamentals for the determination of exchange rates and using the exchange rate to explain economic development may be of limited use for the countries analyzed.
Keywords: 330